Factfulness : ten reasons we're wrong about the world - and why things are better than you think /: ten reasons we're wrong about the world - and why things are better than you think. (2019) - Rosling, Hans; Rosling, Ola, 1975-; Rönnlund, Anna Rosling, 1975-
No abstract available